The Influence of Vertical Resolution on Internal Tide Energetics and Subsequent Effects on Underwater Acoustic Propagation - L. Hiron; M. C. Schönau; K. J. Raja; E. P. Chassignet; M. C. Buijsman; B. K. Arbic; A. Bozec; E. F. Coelho; M. S. Solano (Journal of Advances in Modeling Earth Systems)
Abstract Internal tide generation and breaking play a primary role in the vertical transport and mixing of heat and other properties in the ocean interior, thereby influencing climate regulation. Additionally, internal tides increase sound speed variability in the ocean, consequently impacting underwater acoustic propagation. With advancements in large‐scale ocean modeling capabilities, it is essential to assess the impact of higher model resolutions (horizontal and vertical) in representing internal tides. This study investigates the influence of vertical resolution on internal tide energetics and its subsequent effects on underwater acoustic propagation in the HYbrid Coordinate Ocean Model (HYCOM). An idealized configuration with a ridge, forced only by semidiurnal tides and having 1‐km horizontal grid‐spacing, is used to test two different vertical‐grid discretizations, defined based on the zero‐crossings of horizontal velocity eigenfunctions and the merging of consecutive layers, with seven distinct numbers of isopycnal layers, ranging from 8 to 128. Analyses reveal that increasing the number of layers up to 48 increases barotropic‐to‐baroclinic tidal conversion, available potential energy, and vertical kinetic energy, converging with higher layer counts. Vertical shear exhibits a similar pattern but converges at 96 layers. Increasing the number of isopycnal layers, up to 48, increases the available potential energy contained in high (third‐to‐eighth) tidal baroclinic modes. Finally, sound speed variability and acoustic parameters differ for simulations with less than 48 layers. Therefore, the study concludes that a minimum vertical resolution (48 layers in this case) is required in isopycnal models to accurately represent internal tide properties and associated underwater acoustic propagation.